Fashion design - Jones, Sue Jenkyn (New York : Watson-Guptill Publications, 2002)
A guide to twenty-first century fashion covers career opportunities while gauging the industry today, offering advice on clothing, patterns, fabrics, portfolios, and building a collection
Introduction -- Context -- From manufacture to market -- The body -- Colour and fabric -- In the studio -- The brief -- The final colleciton-and beyond
Includes bibliographical references (page 186) and index
Keywords: Fashion design; Fashion design -- Vocational guidance; Clothing and dress